A report on the practice in industry training in fish capture - Feliciano, Isidro G. (College of Fisheries, University of the Philippines, 1963)
The Philippine is situated on the southwest of the pacific, one of the best known fishing grounds in the world. It is strategically located that most of the oceanic species stay for sometime in our gulfs and bays during their migration from the warm waters of the equator to the Pacific Ocean. It is sad to say that with the presence of this different species in our marine waters still we are fishing a great shortage of it. Very amazing indeed! However, as time goes on we will not suffer on this as our fishermen became educated. The role of fishery graduates in the attempt of our government about the situation can be made by inventing more fishing gears and studying the most scientific ways of catching it. With this, I think it will tend to make our country's subsistence as far as the supply in concerned.